The (Parkland) kids are alright. Issue 1 (March 2020) - Eckstein, Justin
Wounds materialize in the wake of the event, when rhetoric inadequately indexes what is present in a situation. Such a position bypasses ethics from the transcendental ought or the purely descriptive is to an ethics grounded in an immanent occurrence. To give an example of this kind of rhetorical ethics, I turn to an example of a recent wound, the shooting at Marjory Stoneman Douglas High School, where the pathology of gun violence has created a wound that shattered our rhetorical sensorium. In the immediate aftermath, Emma Gonzales, a student and survivor of the Parkland shooting, seized upon this perspective on the wound to forge a new figure, the Parkland Kid, and with it new lines of argument. I argue her capacity to turn a wounding into a new subject illustrates a new rhetorical ethics that is inclusive; she became a subject of the shooting, the new Parkland Kid, that anyone is welcome to join. My contribution departs from the wound as a damaged attachment for its understanding as a productive force.